Voices and views on rural children. A proposal for new approaches (Argentina, mid-20th century) - Salomón, Alejandra Laura (2018)
The present work intends to explore the rural well-being from a historical point of view, through the case of the agricultural colony 17 de Octubre, known after as La Capilla (Florencio Varela, Buenos Aires) founded in 1951 and located in a transitional space between the countryside and the city. In this sense, personal memories and family protographs supports this hypothesis: precariousness of living conditions are not always assumed as such. It confirms the necessity of take into account subjective dimensions of well-being, in intersection with values and aspirations, with time and space coordinates.